Biological stabilization of mine dumps: Shear strength and numerical simulation approach with special reference to Sisam tree - Rai R.; Shrivastva B.K. (My University, 2025)
The stability of mine waste dump is very important for an economic and safety point of view. The biological method is the most popular and eco-friendly approach to stabilize the mine waste dump in the long term. Trees outclass grasses and shrubs for long term stability as the roots of trees are stronger and penetrate deeper. Their roots bind the dump material and form a composite material having high shear strength. The mechanics of stabilization by tress have yet not been fully understood. Moreover, one always refers to biological stabilization of slope qualitatively rather than quantitatively. A numerical simulation tool has been used in the present paper to assess the increased factor of safety of a vegetated dump slope. The Sisam tree was chosen for the present study as it is commonly available in northern India, needs little care and has high economic value. The increased shear strength of the dump mass having tree roots was calculated by shear box test. The tree roots occupy large space, hence, a large size shear box (1.5 m × 1.5 m × 0.75 m) has specifically been designed and fabricated for determining the shear strength of dump root matrix. A small size shear box (0.30 m × 0.30 m × 0.15 m) has also been designed and fabricated to determine the increased shear strength due to small trees. It was observed that the Sisam tree of even moderate size binds the upper layers of mine dump and improve the factor of safety substantially. It was also observed that the stability of dump slope improves with time (i. e. size of tree). © 2010 Springer-Verlag.